The Image Mission 2000
DOI: 10.1007/978-94-011-4233-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Far Ultraviolet Imaging from the Image Spacecraft: 1. System Design

Abstract: Abstract. Direct imaging of the magnetosphere by the IMAGE spacecraft will be supplemented by observation of the global aurora, the footprint of magnetospheric regions. To assure the simultaneity of these observations and the measurement of the magnetospheric background neutral gas density, the IMAGE satellite instrument complement includes three Far Ultraviolet (FUV) instruments. In the wavelength region 120-190 nm, a downward-viewing auroral imager is only minimally contaminated by sunlight, scattered from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 30 publications
(13 reference statements)
2
179
0
Order By: Relevance
“…[7] In this study we use a subset of substorms identified by Frey et al [2004] from images of the northern hemispheric auroral oval made by the far ultraviolet (FUV) instrument on board the IMAGE spacecraft [Mende et al, 2000a[Mende et al, , 2000b. The FUV instrument consisted of a wideband imaging camera (WIC), and two Spectrographic Imagers, SI12 and SI13.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In this study we use a subset of substorms identified by Frey et al [2004] from images of the northern hemispheric auroral oval made by the far ultraviolet (FUV) instrument on board the IMAGE spacecraft [Mende et al, 2000a[Mende et al, , 2000b. The FUV instrument consisted of a wideband imaging camera (WIC), and two Spectrographic Imagers, SI12 and SI13.…”
Section: Methodsmentioning
confidence: 99%
“…The poleward edge of auroral oval emission is often used as a proxy for the location of the boundary between the more poleward open magnetic field lines and the more equatorward closed magnetic field lines, the open-closed magnetic field line boundary (OCB) [e.g., Boakes et al, 2008, and references therein]. Global hemispheric auroral imagery from orbiting spacecraft, such as the Imager for Magnetopause-toAurora Global Exploration (IMAGE) mission [Mende et al, 2000a], thus allows the size of the region enclosed by the auroral oval (the polar cap), and hence the hemispheric open magnetic flux content of the magnetosphere (F pc ), to be estimated [e.g., Milan et al, 2003Milan et al, , 2007. Several studies [e.g., Milan et al, 2003Milan et al, , 2007Milan et al, , 2009aCoumans et al, 2007;DeJong et al, 2007;Hubert et al, 2008;Boakes et al, 2009;Huang et al, 2009] have employed such methods to show that F pc typically increases by ∼25%-35% during the substorm growth phase, while the average F pc at onset is typically between 0.5 and 0.7 GWb (but can be as low as 0.3-0.45 GWb for very weak events and as high as 0.8-1.0 GWb for sawtooth events).…”
Section: Introductionmentioning
confidence: 99%
“…In each case, the mag- netic field line footprint has been estimated using the Tsyganenko 1996 (T96) magnetic field model (Tsyganenko, 1995(Tsyganenko, , 1996, parameterised by appropriately lagged solar wind and IMF observations. Global observations of the auroral oval are provided by the Far UltraViolet (FUV) imager on board the Imager for Magnetopause-to-Aurora Global Exploration (IMAGE) spacecraft (Mende et al, 2000a(Mende et al, , 2000bFrey et al, 2001). The FUV instrument comprises three sensors, each sensor working simultaneously over different wavelength intervals and data from two of which are presented below.…”
Section: Instrumentationmentioning
confidence: 99%
“…The IMAGE SI12 has a gorill system to reject the geocoronal Ly cx emission at 1215.6 A and allow a fraction of the broad auroral Ly cx line profile [Mende et al, 2000a[Mende et al, , 2000b. Since this emission is emitted by excited fast H atoms, the line profile for a given observation geometry depends on the energy spectrum of the incident auroral protons and their pitch angle distribution.…”
Section: Lyman Et Line Profile and Si12 Responsementioning
confidence: 99%